THE EFFECT OF ENTREPRENEURSHIP ATTITUDE, SUBJECTIVE NORMS, AND ENTREPRENEURSHIP EDUCATION ON THE ENTREPRENEURSHIP INTENTION OF CLASS XII STUDENTS OF YAPPA VOCATIONAL SCHOOL DEPOK - Puspitasari, Irni; Eryanto, Henry; Munawaroh (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine whether there is an influence between Entrepreneurial Attitudes,Subjective Norms and Entrepreneurship Education on Entrepreneurial Intentions. Thisresearch was conducted for 9 months staring from April 2020 to January 2021. This study used asurvey methid. In this study, the affordable population was 193 students with a sample of 123students. The multiple linear regression test with the result of the equation Ŷ = 2,950 + 0,245 X1 +0,214 X2 + 0,627 X3. The results of the F test in the ANOVA table are F-count > F0table withvalue of 180,152 > 2,68. This means that the Entrepreneurial Attitude, Subjective Norms, andEntrepreneurship Education simultaneously influence Entrepreneurial Intentions, so that thehypothesis is accepted. The t-test results for Entrepreneurial Attitudes t-count 2,994 > t-table1,980, Subjective Norm t-count 3,398 > t-table 1.980, and Entrepreneurship Education t-count8,873 > t-table 1,980. This means that Entrepreneurial Attitudes have a positiveinfluence on Entrepreneurial Intentions, Subjectives Norms have a positive influence onEntrepreneurial Intention, Entrepreneurial Education has a positive influence onEntrepreneurial Intentions.